KESEDERHANAAN WABICHA DALAM UPACARA MINUM TEH JEPANG - Fajria Noviana (IZUMI, 2015)
The Japanese tea ceremony is called chanoyu in Japanese. It is a multifaceted traditional activity strongly influenced by Zen Buddhism, in which powdered green tea, or matcha, is ceremonially prepared and served to the guests. Wabicha is a style of Japanese tea ceremony particularly associated with Sen no Rikyū that emphasizes simplicity. He refined the art of Japanese tea ceremony equipment and tea house design, with a preference for very simple and very small tea rooms, and natural materials with simpler decoration